WHISTLEBLOWING, KPK INDONESIA DAN CPIB SINGAPURA - Arismaya, Anisa Dewi (Fakultas Ekonomi, Program Studi Akuntansi, 2021)
Whistleblowing is one of the tools used by anti-corruption agencies in Singapore and Indonesia to support the prevention and implementation of an anti-corruption culture. The implementation of Whistleblowing in Indonesia and Singapore has complied with the standard of application, but there are several things that are still obstacles to implementation, including the absence of a law that guarantees the confidentiality of the reporter. This study uses a qualitative descriptive analysis method to explain the differences in the application of Whistleblowing at the KPK and CPIB Singapore corruption eradication institutions. From the results of the study, it can be concluded that CPIB Singapore applies Whistleblowing with complete content and independent application because it has a centralized structure while at the Corruption Eradication Commission, the application of Whistleblowing is not centralized because it is derived from central government institutions and local governments.